2013
DOI: 10.1120/jacmp.v14i2.4075
|View full text |Cite
|
Sign up to set email alerts
|

Local tumor control probability to evaluate an applicator‐guided volumetric‐modulated arc therapy solution as alternative of 3D brachytherapy for the treatment of the vaginal vault in patients affected by gynecological cancer

Abstract: The purpose of this study was to evaluate the applicator‐guided volumetric‐modulated arc therapy (AGVMAT) solution as an alternative to high‐dose‐rate brachytherapy (HDR‐BRT) treatment of the vaginal vault in patients with gynecological cancer (GC). AGVMAT plans for 51 women were developed. The volumetric scans used for plans were obtained with an implanted CT‐compatible vaginal cylinder which provides spatial registration and immobilization of the gynecologic organs. Dosimetric and radiobiological comparisons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…In their experience, the CT compatible vaginal cylinder, through providing spatial registration and immobilization of the gynecologic organs, minimized target volume motion variability allowing 2 mm PTV margin. By reducing cervical target volume motion, this applicator allowed lower rectal dose when compared with BT (44).…”
Section: Accounting For Target Motion: An Ongoing Dilemmamentioning
confidence: 99%
See 1 more Smart Citation
“…In their experience, the CT compatible vaginal cylinder, through providing spatial registration and immobilization of the gynecologic organs, minimized target volume motion variability allowing 2 mm PTV margin. By reducing cervical target volume motion, this applicator allowed lower rectal dose when compared with BT (44).…”
Section: Accounting For Target Motion: An Ongoing Dilemmamentioning
confidence: 99%
“…The rectal dose to 1 cc (d 1cc ) was (5.09 vs. 6.05 Gy, P=0.02), the bladder d 1cc (6.78 vs. 8.76 Gy, P=0.04) and the median target coverage by the 100% isodose line was (99.1% vs. 50.7%, P<0.05); all favoring SBRT plans (the study however was limited by BT dose prescription to point A) (41). Similarly, the volumetric modulated arc therapy (VMAT) dosimetric plans [generated for 51 gynecologic cancer patients receiving the initial 45-50.4 Gy via three dimensional conformal radiotherapy (3DCRT) and a boost of 6 Gy for maximum dose (d max ) with comparable bladder and bowel dose; however, the integral dose and the PTV coverage favored BT (44). These results are discordant with Georg et al dosimetric study in which image guided BT was superior to EBRT plans using either photon or proton radiotherapy.…”
Section: Newer Techniques May Offer Dose Distribution Not Exceedinglymentioning
confidence: 99%
“…Being a relatively new technique in cervical cancer radiation therapy, it has yet to be evaluated in the literature to the extent of other alternatives [208]. That said, a pioneering work by Pedicini et al in 2012 revealed that SBRT delivered in VMAT fashion accomplished an 11% lower rectal d1cc, and a 10% lower bladder d1cc compared to high dose-rate brachytherapy (HDR BT), while requiring nearly 60% less treatment time [206]. Despite this, the mean PTV doses with this technique were up to 55% lower than HDR BT which significantly diminished their tumour control probability.…”
Section: Volumetric-modulated Arc Therapy and Stereotactic Body Radiotherapymentioning
confidence: 99%
“…VMAT needed 28% less monitor units compared with IMRT, and treatment duration reduced from 11 to <3 minutes for a dose of 6 Gy. Pedicini et al111,112 compared VMAT, IMRT and 3D-CRT using a vaginal cylinder for vaginal immobilization to 3D brachytherapy. The cylinder was able to reduce the movement in the VMAT course and reduced planning target volume margin to 2 mm.…”
Section: Custom or Standard Radiotherapy Planningmentioning
confidence: 99%